Experimental and numerical investigations of latent thermal energy storage using combined flat micro-heat pipe array–metal foam configuration: Simultaneous charging and discharging. (June 2021) - Liang, L.; Diao, Y.H.; Zhao, Y.H.; Wang, Z.Y.; Chen, C.Q.
Abstract: Simultaneous charging and discharging (SCD) of the latent thermal energy storage (LTES) can improve the flexibility of solar thermal systems and ensure the continuity of energy supply. Experiments and numerical simulation are conducted in this study to reveal the SCD thermal behavior of LTES device using flat micro-heat pipe array–metal foam composite structure. The effects of heat transfer fluid (HTF) temperature, volumetric flow, initial phase change material (PCM) state, and metal foam are analyzed. Results show that PCM absorbs heat from hot HTF or releases heat to cold HTF at the beginning depending on the PCM and HTF temperatures. The SCD eventually reaches an approximate steady state, cold HTF exchanges heat directly with hot HTF, power and PCM temperature remain unchanged. Low cold HTF temperature quickly reaches steady state and low final PCM temperature but has no influence on steady state power. PCM initial state and metal foam porosity do not affect the steady state power and final PCM temperature. However, they affect the time to reach steady state. Metal foam pore density has no obvious effect on SCD. SCD has more stable discharging performance than single discharging, especially when the cold HTF temperature is high. Highlights: LTES device based on FMHPA and metal foam is designed. Operating mode of simultaneous charging and discharging (SCD) is investigated. Effects of HTF temperature and velocity on SCD are analyzed experimentally. Effects of initial state and metal foam parameters are investigated numerically. Thermal performances of SCD are compared with single charging and discharging.